A novel stop codon mutation of TSPAN12 gene in Chinese patients with familial exudative vitreoretinopathy. (4th March 2022) - Zou, Gang; Qi, Rui; Ma, Meijiao; Fu, Shangyi; Liang, Qingnan; Bi, Xiaojun; Wang, Chanjuan; Hu, Xuejun; Cai, Yujuan; Sheng, Xunlun
ABSTRACT: Background: Familial exudative vitreoretinopathy (FEVR) is a group of inherited eye diseases characterized by premature arrest of retinal vessel development. The purpose of our study was to characterize the genetic causes and clinical features in eight Chinese families with FEVR using next-generation sequencing (NGS) technology. Materials and methods: Eight families with FEVR were included in genetic and clinical analyses. We screened the proband and the parents in eight pedigrees with FEVR using targeted NGS approach and in silico analysis to determine the causative mutation for their family's phenotype. Results: Four cases (4/8, 50.0%) were confirmed to harbor mutations in known genes, including 3 novel mutations and one previously reported mutation. Among the detected mutations, TSPAN12 accounted for 75% (3/4). We identified a novel stop codon of TSPAN12, a heterozygous missense mutation NM_012338.4:c.633T>A, NP_036470.1:p.Tyr211Ter involved in highly conserved residues in the proband. Retrospective analysis of its clinical manifestation showed that the mutant carrier presented mild clinical features. Conclusions: We found the novel stop codon mutation p.Tyr211Ter in the TSPAN12, which creates a milder phenotype. Discovery of this novel mutation expands the mutation spectrum of TSPAN12, and would be valuable for future genetic disease diagnosis.